Kosovo : Technical Assistance Report-Enhancing Social Protection Cash Benefits. (IMF Staff Country Reports; Country Report ;, 2016)
This paper assesses the sustainability of the public pension system, discusses recent and proposed changes to veterans' benefits, and reviews the effectiveness of social assistance in Kosovo. The social transfer programs created in the wake of Kosovo's independence are narrower in scope than similar programs in other European emerging economies. Poverty, the main policy challenge of the country, can be addressed through employment-friendly economic growth and pro-poor social spending. Kosovo's highly inequitable current system of social cash transfer represents a departure from the fiscally sustainable and conceptually homogenous structure of the early 2000s.